Low to moderate prenatal alcohol consumption and the risk of selected birth outcomes: a prospective cohort study - Lundsberg, Lisbet S. (Ann Epidemiol, 2014)
PURPOSE: Estimate whether low to moderate prenatal alcohol exposure is associated with selected birth outcomes. METHODS: Low to moderate prenatal alcohol drinking and effects on low birth weight, preterm delivery, intrauterine growth restriction (IUGR), and selected neonatal outcomes were evaluated among 4,496 women and singleton infants. Odds ratios (OR) and 95% confidence intervals (CI) were calculated using multivariable logistic regression, controlling for confounding variables. RESULTS: Early pregnancy drinking was associated with reduced odds of low birth weight, OR 0.66 (95% CI 0.46, 0.96) and birth length < 10(th) percentile, OR 0.74 (95% CI 0.56, 0.97). Drinking during the first 3 months showed lower odds for birth length and head circumference < 10(th) percentile, OR 0.56 (95% CI 0.36, 0.87) and OR 0.69 (95% CI 0.50, 0.96), respectively. Third trimester drinking was associated with lower odds for low birth weight, OR 0.56 (95% CI 0.34, 0.94) and preterm delivery, OR 0.60 (95% CI 0.42, 0.87). CONCLUSIONS: Our results suggest low to moderate alcohol exposure during early and late gestation is not associated with increased risk of low birth weight, preterm delivery, IUGR and most selected perinatal outcomes.